2014
DOI: 10.1159/000355177
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic Kidney Disease with Renal Calculi Treated by Percutaneous Nephrolithotomy: A Report of 11 Cases

Abstract: Objective: To evaluate the efficacy and safety of percutaneous nephrolithotomy (PCNL) in the treatment of congenital autosomal dominant polycystic kidney disease (ADPKD) with renal calculi. Methods: A total of 11 cases of ADPKD with renal calculi were retrospectively studied. All cases were treated by PCNL and clinical parameters such as age, sex, stone burden, operation time, blood loss, complications and perioperative serum creatinine levels were collected and analyzed. All patients were routinely followed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Zhang and colleagues [8] reported 12 satisfactory USG PCNL for eleven ADPKD patients in their study. In our study, the FG group achieved a 96 % of successful access.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Zhang and colleagues [8] reported 12 satisfactory USG PCNL for eleven ADPKD patients in their study. In our study, the FG group achieved a 96 % of successful access.…”
Section: Discussionmentioning
confidence: 92%
“…Satisfactory outcomes during PCNL are often dependent on the optimal access to the kidney. Both FG and USG percutaneous renal access for PCNL in ADPKD patients have been reported in several studies [3,[6][7][8]16]. Zhang et al [8] reported twelve satisfactory USG PCNL in eleven ADPKD patients without major complications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations